Rifabutin Induced Vitritis in a HIV Patient Co-Infected with Tuberculosis: a Case Report - Dr. Sri Rama (International Journal of Allied Medical Sciences and Clinical Research, 2020)
A 48-year-old newly diagnosed HIV infected woman presented with ulcers in mouth, weight loss, breathlessness since 5-6 months, she was diagnosed with oral Candidiasis, Pneumocystis carnii Pneumonia and tubercular lymphadenitis. Seventy days after starting on ATT, she presented with complaints of blurring of vision in the right eye. Opthalmic evaluation revealed severe vitritis in the absence of posterior uveitis. The causality of vitritis to Rifabutin intake was probable as per WHO probability scales. It took 6 weeks for complete spontaneous resolution of Vitritis and the visual acuity returning to 6/6 in both eyes. Rifabutin toxicity can occur throughout the course of treatment that has to be monitored based on clinical manifestations.